Graz 1914 Der Volkskrieg auf der Straße - Thonhofer, Bernhard (2018)
This dissertation examines the outbreak of the First World War in Graz by means of a microhistorical approach. Consequently, this dissertation reveals that the social cohesion of the city has fundamentally changed during the first months of the war. Due to people's various different notations concernig the right way of living and, particularly, the proper way of warfare, countless conflicts as well as cooperations arose in the city.